Interpersonal Functioning in Pediatric Bipolar Disorder - Keenan-Miller, D; Miklowitz, D (2011)
This article reviews studies of interpersonal functioning, social cognition, and life stress in children and adolescents with bipolar disorder (BD). Peer and family relationships of youth with BD are impaired in comparison to healthy controls and youth with attention-deficit hyperactivity disorder (ADHD). Social-cognitive deficits, such as impaired facial affect recognition, may underlie these interpersonal difficulties. Affect among youth with BD is particularly dysregulated in interpersonal situations and is often characterized by elevated anger and frustration. Preliminary evidence suggests that life stress is associated with course. Further research in this area must consider the role of comorbidity and family environment in determining psychosocial outcomes. Studies should aim to incorporate naturalistic and developmentally appropriate measures of social functioning and examine the impact of psychosocial interventions in modifying social dysfunction. © 2011 American Psychological Association.